1974
DOI: 10.1016/0005-2736(74)90044-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the valinomycin-induced potassium ion leak from liposomes with potassium thiocyanate enclosed

Abstract: SUMMARYThe kinetics of the valinomycin-induced K + leak from egg lecithin liposomes with KCNS enclosed were studied by measuring the initial increase of the leak following the addition of the ionophore. Variation of liposome and valinomycin concentrations enabled a discrimination between the affinity of the ionophore for the lipid bilayer and the turnover rate of the transport process. The results indicate that valinomycin is distributed immediately between the outer liposomal bilayer and the aqueous phase. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

1975
1975
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…Our measured value of AH:~ is in good agreement with the values measured by Johnson and Bangham (1969) and Blok et al (1974) for 42K+ flux and KCNS efflux (respectively) through phospholipid membranes.…”
Section: [M+]o and [Ans-]o : D[ans-]]dt-k3b[i]t K2 K3 [M+]~ [Ans-]~ (supporting
confidence: 84%
See 3 more Smart Citations
“…Our measured value of AH:~ is in good agreement with the values measured by Johnson and Bangham (1969) and Blok et al (1974) for 42K+ flux and KCNS efflux (respectively) through phospholipid membranes.…”
Section: [M+]o and [Ans-]o : D[ans-]]dt-k3b[i]t K2 K3 [M+]~ [Ans-]~ (supporting
confidence: 84%
“…It has been shown by de Gier, Mandersloot and van Deenen (1968) that the nonelectrolyte permeability of liposomes increases with increasing degree of unsaturation and decreasing chain length. The lipid bilayer experiments were carried out at least 30~ above their phase transition temperature, whereas the k3b values of Table 6 are for a temperature 10 ~ above T m. The transport reaction has a large activation enthalpy (AH~: = 16.3 + 0.5 kcal) and extrapolation of the measured rates to 53~ (30~ above Tin) gives a k3b value of 310sec -1 in good agreement with the value of Blok et al (1974). The remaining difference between this value and the values for mitochondria (Haynes et al, 1974) and the lipid bilayer (Benz et al, 1973) may be due to the presence of integral proteins in the former system and the presence of organic solvents in the latter system.…”
Section: [M+]o and [Ans-]o : D[ans-]]dt-k3b[i]t K2 K3 [M+]~ [Ans-]~ (mentioning
confidence: 71%
See 2 more Smart Citations
“…The possibility that ANS permeation may be induced or increased by a valinomycin potassium complex is suggested by the observation that this complex may be associated with anions (Davis & Tosteson, 1971;Blok, De Gier & Van Deenen, 1974) and, more specifically, with ANS in water and chloroform (Feinstein & Felsenfeld, 1971) and possibly in phospholipid membranes (Haynes, 1972). Further, Feinstein and Felsenfeld (1971) have shown that the presence of valinomycin and potassium chloride increases the partition of ANS from water into chloroform.…”
mentioning
confidence: 93%